On The Cooperative and Doppler Diversity for Amplify-and-Forward Relay Network - Rabbi, M. F.; Kamarul Hawari, Ghazali (Asian Research Publishing Network (ARPN), 2015)
This paper investigates Cooperative and Doppler diversity for Amplify-and-Forward (AF) relay network assuming the channel between Mobile Station (MS)s and Relay Station (RS)s as well as the channel between the RSs and Base Station (BS) are nonstationary. More specifically, this paper analyzes and demonstrates how both the Doppler and cooperative diversities can be achieved to improve the system performance of an AF relay network in high user mobility scenario. To facilitate the analysis, a model for 011hogonal Frequency Division Multiple Access (OFDMA) based AF relay is developed. The time varying channel is modeled using Basis Expans ion Model (BEM). Using both models we present efficient signal detection methods which can exploit the Doppler spread to improve Symbol Error Rate (SER) performance. Theoretical analysis together with simu lation results are presented to demonstrate the improvement on system performance.